Towards a sustainable tourism zone in the wider Caribbean - Hatton, Miguel Ceara (ACS Port of SpainTT, 1998)
Provides an overview of the movement of tourism by regions of the world and places the countries of the Wider Caribbean into this context. Presents some figures on tourism trends in Association of Caribbean States countries. Concentrates on an assessment of the reasons for creating a sustainable zone within the ACS, and progress made in this area.